A case report of enzalutamide administration in a dialysis-dependent patient with castration-resistant prostate cancer. (March 2018) - Tsang, Erica S; de Haan, Marie; Eigl, Bernhard J
Enzalutamide, an androgen receptor signaling inhibitor, is a standard of care treatment for metastatic castration-resistant prostate cancer. We present the first reported case of enzalutamide in a patient with end-stage renal disease, on dialysis. While there were no significant toxicities, a sustained increase in systolic blood pressure was maintained after starting enzalutamide, suggestive of a degree of drug accumulation. Further evaluation of novel hormonal agents in end-stage renal disease patients should be encouraged as this population is typically excluded from clinical trials.